ANALISIS WORTWAHL PADA MEDIA KARTU QUOTES BAHASA JERMAN PRODUK ECOBITES - Nuri, Nazilatul Alfi; Wahyuningsih, Fahmi; Lestari, Tri Edliani (LATERNE, 2025)
This study aims to identify the form and meaning of word choices in German-language quote cards produced by ECOBITES as part of their marketing strategy. Using a descriptive qualitative approach and content analysis techniques, this study examines the words, phrases, and sentences of five quote cards. The results of the study show that the word choices include lexical, contextual, connotative, and denotative meanings lexical, contextual, connotative, and denotative meanings with an informal and emotional style. Words such as Freude and Glück are analyzed semantically based on Frege and Gadamer's theories, revealing the subjective understanding of readers. These word choices serve to build a strong brand identity, enhance emotional closeness with consumers, and strengthen the appeal and differentiation of products in the international market.